The practices and beliefs of dental professionals regarding the management of patients taking anticoagulant and antiplatelet drugs - Niamh Kelly; Laura Beaton; Jennifer Knights; Douglas Stirling; Michele West; Linda Young (Nature Publishing Group, 2023)
Abstract Aim This study aimed to inform the implementation of the updated Scottish Dental Clinical Effectiveness Programme (SDCEP) guidance, 'Management of Dental Patients taking Anticoagulant or Antiplatelet Drugs', and to determine training needs by investigating dental professionals' current practice and beliefs regarding management of patients taking these medications. Methods Dental professionals were recruited via the NHS Education for Scotland Portal. The online questionnaire collected demographic information, data on current practice and information about beliefs regarding behaviours related to the management of patients on anticoagulant or antiplatelet medication. Quantitative data were analysed using SPSS and subjected to frequency calculations, t-tests, one-way ANOVA and linear regression. Qualitative data were collected via free text boxes and analysed using thematic analysis. Results One hundred and fifty-seven participants responded to the questionnaire. The majority of respondents stated they were aware of the guidance and always based their practice on it. The majority of respondents always assessed the patient's individual bleeding risk prior to dental procedures. Most respondents felt that they did not know how to appropriately manage patients taking low doses of low molecular weight heparins (LMWH), and only 38% of respondents always followed SDCEP guidance about direct oral anticoagulants (DOAC) medication and procedures with a low associated risk of bleeding. Discussion This study demonstrates a need for further educational support surrounding LMWHs and management of patients on DOAC medication. Time and remuneration represent barriers to guidance implementation in primary care. Conclusion There is good awareness and adherence to the guidance in primary care settings, however training needs were identified to support implementation.